Recent Advances in Research on Lacquer Allergy - Xiao-ming Ma; Rong Lu; Tetsuo Miyakoshi (Allergology International, 2012)
Allergic contact dermatitis caused by contact with lacquer sap and lacquerware affects the welfare of lacquer workers and the lacquerware industry. Many studies of the mechanism of urushiol allergy, including animal models, have been carried out and have established several hypotheses. In order to provide a comprehensive understanding of lacquer allergy, we review recent advances in the research on lacquer allergy including the chemical properties of lacquer lipid components, allergic mechanism analyses, immunological explanations, allergy medications, and the prevention combined with the research results from our laboratory.